Application of fungicides during leaf fall to control apple scab (Venturia inaequalis) in the following season - Beresford, R.M.; Wood, P.N.; Shaw, P.W.; Taylor, T.J. (New Zealand Plant Protection, 2008)
Leaf fall applications of fungicides to reduce scab in apple orchards were investigated to reduce reliance on summer fungicides that can cause trace chemical residues on harvested fruit Two applications of fungicides including captan tolyfluanid myclobutanil and urea were made at 1020 and 5060 leaf fall in four orchard trials in Nelson and Hawkes Bay using the cultivars Royal Gala Braeburn Fuji and Sciros/Pacific Rosetrade; Trial orchards received standard spring and summer fungicide programmes that complied with Integrated Fruit Production and were monitored for leaf and fruit scab in December and at harvest Significant reductions in leaf or fruit scab occurred in three out of five comparisons involving different sites years and cultivars suggesting that autumn applications can reduce scab in the following season Captan and tolyfluanid appeared most useful for autumn application Myclobutanil should not be used because of the fungicide resistance risk Results with urea were variable